Occurrence of Quadruplets in Nelore Cattle: A Case Report - Miguel Ferreira de Camargo, Gregório; Brito Sales, Lucas Henrique; Bermal Costa, Raphael (Journal of Advanced Veterinary Research, 2020)
Cattle are monotocous species and cow usually deliver one calf per birth.Â  The present report has the aim to notify the birth occurrence of quadruplets of a Nelore cow: first time in scientific literature for this breed. The report presents negative and positive consequences of event.